PANDEMIC INFLUENZA A (H1N1) PDM 09 IN THE SEASON 2015/2016: ANALYSIS OF FATAL OUTCOMES IN CHILDREN - V. N. Timchenko; O. I. Afanas'eva; E. A. Dondurey; O. V. Bulina; V. S. Afanas'eva; L. M. Pochinyaeva; E. F. Gorbunov (LLC "Diagnostics and Vaccines", 2017)
The analysis of the characteristics of the current influenza A(H1N1) pdm 09 at 624 children in the 2015/2016 season. For severe illness (5%) characterized by short incubation period, lack of initial period, acute or acute onset with rapid development of multiorgan failure, prolonged febrile body temperature (up to 5-6 days or more) in the absence of complications, a prolonged severe intoxication (4-5 days or more), a significant frequency of diarrhea syndrome (10,2%), hemorrhagic syndrome (5.3%), exacerbation of comorbidity (20%), combined  with other viral infections  - herpes, rotavirus, enterovirus and others (33%).In the clinical analysis of blood - leukopenia (33.9%), leukocytosis (14.5%) with neutrophilic  shift (11.3%), neutrophilia (51.6%), monocytosis (45.2%), lymphocytosis (9.7%), thrombocytopenia, anemia, accelerated erythrocyte sedimentation rate moderately; in the biochemical analysis of blood, hypernatremia, increase in the concentration of lactate, hyperfermentemia (ALT, AST, ALP, LDH, CPK), hypoproteinemia, dysproteinemia, increased CRP, increased creatinine and urea, increase of procalcitonin (PCT). In the structure of complications of pneumonia was 6%, stenosing laryngotracheitis - 9.8%, obstructive bronchitis - 14.5%. Two unvaccinated against influenza in infants who become ill during the epidemic period for influenza and SARS from homes with a typical clinical picture, died from severe (toxic) form of pandemic influenza. Pandemic influenza occurred at the background of severe immunosuppression (atrophy of the thymus, depletion  of follicles of peripheral organs of immunogenesis - spleen, lymph nodes, tonsils). The main cause of death was the development of multiple organ failure with rapid progressive lesion of the vital organs.